মুক্ত মনের আসর Begum Rokeya Smriti Kendro, Payrabondo, Mithapukur, Rangpur - Islam, Fariba (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2023.